2019
DOI: 10.1007/s00348-019-2823-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the internal flow in freezing water droplets on a cold surface

Abstract: The study of a freezing droplet is interesting in areas, where the understanding of build up of ice is important, for example, on wind turbines, airplane wings and roads. In this work, the main focus is to study the internal motion inside freezing water droplets using particle image velocimetry and to reveal if mechanisms such as natural convection and Marangoni convection have a noticeable influence on the flow within the droplet. The flow has successfully been visualized and measured for the first 25% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…This flow is a result of the circulation flow near the contact line and the descent of cool water near the cap of the droplet. This second circulation flow is similar to the internal flow field of freezing water droplets measured by Karlsson et al (2019). The droplets' volumes and the temperature in the present study are lower than the corresponding ones for Karlsson et al's measurement.…”
Section: Temperature and Velocity Fields For The Impinged Dropletsupporting
confidence: 85%
“…This flow is a result of the circulation flow near the contact line and the descent of cool water near the cap of the droplet. This second circulation flow is similar to the internal flow field of freezing water droplets measured by Karlsson et al (2019). The droplets' volumes and the temperature in the present study are lower than the corresponding ones for Karlsson et al's measurement.…”
Section: Temperature and Velocity Fields For The Impinged Dropletsupporting
confidence: 85%
“…The experimental setup can be viewed in Figure 2. The set up is similar to the experimental setup presented by Karlsson et al [30,31] with the modification that the laser is now directed from the side instead of below. This was done so that the plates were not limited to transparent materials.…”
Section: Methodsmentioning
confidence: 99%
“…In the numerical analysis, the Marangoni effect was not included, but they showed that the buoyancy force and the internal natural convection were important for the internal flow. Furthermore, Karlsson et al [30] experimentally showed that there is a turn in the internal flow of a freezing water droplet. A probable cause for this is that the Marangoni effect generates a flow along the surface and up the middle of the droplet in the beginning of the freezing process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations